Kontestasi Penjor Galungan – Kuningan di Bali Visualisasi Doa Petisi secara Demonstratif untuk Kemakmuran pada Era Masyarakat Tontonan - Anantawikrama Tungga Atmadja; Nengah Bawa Atmadja (Pusat Kajian Bali Universitas Udayana, 2016)
This article is part of the fundamental research carried out for two years (2013-2015). The research method is qualitative which refers to the critical paradigm. The research location is villages representing various districts in Bali and Denpasar city. The results showed that the use of Penjor on Galunga and Kuningan holy day is common in Bali. Penjor is a ritual objects made from a piece of bamboo which its end is intentionally left curved, decorated with various ornaments of young coconut leaves or palm leaves and other supplies. Penjor is installed on the roadside in front of the Balinese family compound’s entrance. Penjor does not only have an artistic value, but it is also rich in symbolic meaning such as visualization of petition prayer addressed to the Hindu deities and dewa pitara (ancestor). The goal is to achieve prosperity for the entire family in the Balinese community. This article is expected to provide a broader understanding to Hindus about Penjor. Penjor is not only a cultural object with artistic values, but it also contains a hidden meaning, namely the prayer of petition in the sociology of religion.